2018
DOI: 10.22616/erdev2018.17.n116
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of quality management in small and medium enterprises: problems and solutions

Abstract: Abstract. The benefits of Quality Management are widely recognized following reports of its successful implementation in many large companies. It has led to these companies becoming highly competitive both locally and internationally through the production of quality products that meet customer requirements at the lowest cost, significantly increasing their market share and profitability. Quality standards make life safer, they create a level playing field on which to compete, they allow access to state-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As reported by the authors of the articles (Palacios Guillem, 2019;Santos et al, 2011), the mentioned ISO 9001, ISO 14001 and EMAS systems are the most frequently implemented in SMEs. According to the literature review, it was shown that research in the area of ISO 9001 in SMEs mainly concerned: motivation and benefits from implementation (Khan and Farooquie, 2016;Magodi et al, 2022;Vasilevska and Rivza, 2018;Zimon et al, 2018), main problems occurring during implementation and certification (Unterreiner and Gisbert Soler, 2019), as well as the impact of increasing customer satisfaction with product quality (Usman et al, 2019). In the case of the ISO 14001 system and the EMAS system in SMEs, the research concerned, for example: the impact of the system on the substantive results of the company (Johnstone, 2022), type and application of sustainability controls (Johnstone, 2021), factors, barriers and benefits of implementation (Salim et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As reported by the authors of the articles (Palacios Guillem, 2019;Santos et al, 2011), the mentioned ISO 9001, ISO 14001 and EMAS systems are the most frequently implemented in SMEs. According to the literature review, it was shown that research in the area of ISO 9001 in SMEs mainly concerned: motivation and benefits from implementation (Khan and Farooquie, 2016;Magodi et al, 2022;Vasilevska and Rivza, 2018;Zimon et al, 2018), main problems occurring during implementation and certification (Unterreiner and Gisbert Soler, 2019), as well as the impact of increasing customer satisfaction with product quality (Usman et al, 2019). In the case of the ISO 14001 system and the EMAS system in SMEs, the research concerned, for example: the impact of the system on the substantive results of the company (Johnstone, 2022), type and application of sustainability controls (Johnstone, 2021), factors, barriers and benefits of implementation (Salim et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is questionable to what extent the mentioned frameworks are feasible to match the contextual needs of PHOs. Concerning the feasibility of the frameworks for micro or small organizations, such as physical therapy PHOs, 2 areas are mentioned specifically: (1) a lack of coherent context-specific outcome metrics for quantitative evaluation 4 , 7 , 15 and (2) the bureaucratic character and complexity, hampering an organization's need for change in a dynamic environment. 4 , 5 …”
mentioning
confidence: 99%